Trends in influenza A virus genetics: Can we predict the natural evolution of a H5N1 Z? - Brown, Earl G.; Sattar, Syed A.; Tetro, Jason A.; Liu, Jinhua (Université d'Ottawa | University of Ottawa, 2008)
We reflect here on the issues pertinent to the evolution and host interactions of influenza A viruses (FLUAV) in general but with a focus on the current highly pathogenic avian influenza genotype H5N1 Z and its risk of becoming a determinate human pathogen. Influenza viruses evolve primarily by adaptation and reassortment that involves nucleotide or genome segment substitutions respectively. Although the introduction of a new subtype into a new host has been presumed to involve reassortment of genome segments, we propose a model of evolution to a new host that is mainly dependant on adaptive processes. Chronicling observations of previous human adaptive mutations in H5N1 Z, as well as mammalian and pandemic FLUAV strains of the past, we indicate that evolution can be tracked and the emergence of a pandemic strain may be at least in some sense predicted. Thus we propose that the greatest likelihood of H5N1 Z-like strains emerging in humans is by adaptation in humans although this may involve subsequent reassortment. We further extrapolate from studies of experimental evolution that 5 to 10 mutations through 10 to 20 passages in humans are required to allow a pandemic strain to evolve. We suggest that the high and increasing prevalence of H5N1 Z in domestic and wild aquatic bird reservoirs in concert with human and animal transmission will lead to the spread of virulence promoting genes to viruses infecting these species associated with increased severity of influenza infections.
Keywords: influenza A virus; genetics; evolution; H5N1 Z; host-range; adaptation; pandemic